2002
DOI: 10.1002/jmv.10228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of measles sequences from Pune, India

Abstract: The goal of this study was to conduct the initial genetic characterization wild-type measles viruses currently circulating in India. Reverse transcription-polymerase chain reaction detected measles RNA in 11 of 14 throat swabs collected from sporadic and outbreak-associated cases in the city of Pune, during 1996-1998. Sequence analysis of the H and N genes showed that six sequences were genotype D4, three were genotype D8, and two were genotype A. Continued virologic surveillance in other areas of India as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
3
23
2
Order By: Relevance
“…Molecular studies in India have detected the presence of measles virus and described the circulation of the indigenous genotypes D4, D7, D8 and A [30,32]. Although circulation of D4 and D8 have been documented since 1996 on the Indian subcontinent [32], this time, we found only genotype D8 and one genotype A vaccine-associated case in the studied epidemic areas.…”
Section: Discussioncontrasting
confidence: 50%
“…Molecular studies in India have detected the presence of measles virus and described the circulation of the indigenous genotypes D4, D7, D8 and A [30,32]. Although circulation of D4 and D8 have been documented since 1996 on the Indian subcontinent [32], this time, we found only genotype D8 and one genotype A vaccine-associated case in the studied epidemic areas.…”
Section: Discussioncontrasting
confidence: 50%
“…In 2005, sporadic outbreaks were reported in Chiba and Ibaraki Prefectures, caused by the Palau type D5. In Asian countries, several different indigenous genotypes have been reported: H1 in China [Xu et al, 1998], G2 in Indonesia and Malaysia [Rota et al, 2000], D4 in India [Wairagkar et al, 2002], D3 in Papua New Guinea [Miki et al, 2002], and D7 in Australia [Chibo et al, 2003]. D8 in Nepal [Truong et al, 2001] and D9 in Australia [Chibo et al, 2003] were also reported.…”
Section: Discussionmentioning
confidence: 90%
“…Genotype A is often due to vaccine strains but has been found in several sporadics cases around the world [Wairagkar et al, 2002;Riddell et al, 2005]. The wild type or vaccine nature of these strains could not be confirmed.…”
Section: Genetic Analysis Of Measles Strainsmentioning
confidence: 96%